2022
DOI: 10.3389/fonc.2022.991165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pyroptosis-related lncRNA signature and AC005253.1 as a pyroptosis-related oncogene in prostate cancer

Abstract: BackgroundPyroptosis and prostate cancer (PCa) are closely related. The role of pyroptosis-related long non-coding RNAs (lncRNAs) (PRLs) in PCa remains elusive. This study aimed to explore the relationship between PRL and PCa prognosis.MethodsGene expression and clinical signatures were obtained from The Cancer Genome Atlas and Gene Expression Omnibus databases. A PRL risk prediction model was established by survival random forest analysis and least absolute shrinkage and selection operator regression. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In vitro experiments revealed that silencing AC005253.1 inhibited the proliferation, migration, and invasion of PCa cells. [ 93 ] It is evident that ncRNAs associated with scotomies can offer new avenues for clinicians to develop novel drugs. Overall, the role of ncRNAs in the process of cancer cell pyroptosis is intricate, and further experiments are required to investigate precise interventions in different ncRNA-mediated cell pyroptosis and develop more biomarkers and therapeutic targets (Fig.…”
Section: Role Of Pyroptosis In Pcamentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro experiments revealed that silencing AC005253.1 inhibited the proliferation, migration, and invasion of PCa cells. [ 93 ] It is evident that ncRNAs associated with scotomies can offer new avenues for clinicians to develop novel drugs. Overall, the role of ncRNAs in the process of cancer cell pyroptosis is intricate, and further experiments are required to investigate precise interventions in different ncRNA-mediated cell pyroptosis and develop more biomarkers and therapeutic targets (Fig.…”
Section: Role Of Pyroptosis In Pcamentioning
confidence: 99%
“…[ 98 ] Yu et al identified AC005253.1, an LncRNA associated with PCa pyroptosis, and reported that the inhibition of AC005253.1 expression suppressed the viability, migration and invasion of PCa cells, significantly increased the expression of AIM2 inflammasome, and promoted the pyroptosis in PCa cells. [ 93 ] In view of the findings above, the induction of pyroptosis in PCa cells can be targeted as a new strategy to inhibit tumor growth.…”
Section: Role Of Pyroptosis In Pcamentioning
confidence: 99%
See 1 more Smart Citation